(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
University educators in interior design have a pivotal role in shaping future professionals who are equipped to address pressing environmental challenges. As the discourse on climate change intensifies, it is imperative that interior design education aligns with the principles of sustainable development. The construction industry significantly impacts the environment, and interior design projects are no exception. To mitigate this, educators must instill in students a deep understanding of sustainable practices, including reuse, recycling, the adoption of eco-friendly and locally sourced materials, and the integration of energy-efficient technologies. By incorporating sustainable design courses into interior design education, universities can equip future professionals with the knowledge and skills needed to develop resource-efficient, climate-responsive, and ecologically responsible designs. This article will explore the importance of integrating sustainable design principles into interior design curricula through a comparative study conducted by Samarkand State Architecture and Construction University (Samarkand, Uzbekistan). By analyzing the survey results from this institution, the research aims to develop effective educational programs that equip students with the necessary knowledge and skills to address ecological challenges in Uzbekistan while fostering a new generation of environmentally conscious designers.